(untitled) (Research, Society and Development, 2022)
Objective: to map the available protocols for communicating bad news in health for such a scientific contribution. Method: The scope review protocol will be based on the Joanna Briggs Institute guidelines and the selection of studies will follow the guidelines proposed in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. To record development intent and scientific availability, the protocol was registered in the Open Science Framework platform nº osf.io/sgev2. For the scope of the review, literature that includes evidence to answer the guiding question will be considered: What are the protocols for communicating bad news available to health professionals?. The databases used will be: PubMed/MEDLINE, Virtual Health Library, Cochrane, Embase, Web of Science and Portal of Periodicals of the Coordination for the Improvement of Higher Education Personnel. As gray literature will be adopted: google scholar, the Brazilian Digital Library of Theses and Dissertations and Open Grey. The research will take place systematically, in pairs and independently. The studies will be directed to the EndNoteWeb manager to file and delete duplicate articles. The selected references will be sent to the Rayyan-Intelligent Systematic Review software for the reading of titles and abstracts and classification using the inclusion and exclusion criteria. In case of discrepancy, a third reviewer may intervene. The next step consists of reading the selected studies in full and re-screening them using the aforementioned criteria. The data will be presented in such a way as to provide the reader with a robust and up-to-date view of the availability of protocols for communicating bad news in health. In the discussion, relevant aspects will be pointed out and interrelated in a narrative way.